Co-precipitation method for the preparation of fine ferroelectric BaBi2M2O9 - Gaikwad, S. P.; Potdar, HS; Samuel, V; Ravi, V (Ceramics International, 2005)
A simple co-precipitation technique had been successfully applied for the preparation of pure fine powders of single phase BaBi2Nb2O9. Ammonium hydroxide and ammonium oxalate were used to precipitate Ba2+, Bi3+ and Nb5+ cations simultaneously. No pyrochlore phase was formed while heating powder at 800 degrees C and pure BaBi2Nb2O9 phase was found to be formed by X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 100. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: dielectric properties; Electron microscopy; ferroelectric properties; powders chemical preparation

Preparation of nanocrystalline ferroelectric CaBi2Ta2O9 by the urea method - Gaikwad, S. P.; Pasricha, R; Ravi, V (Ceramics International, 2005)
A precipitate was formed when a aqueous solution of CaCl2, BiCl3, TaF5 and urea in stoichiometric ratio (total metal cations to urea ratio is 5) is heated on a water bath. This precipitate on decomposition at 600 degrees C yielded the nanocrystallites of ternary oxide CaBi2Ta2O9 (CBT) as confirmed by X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). Ferroelectric hysteresis loop parameters such as remnant polarization (P-r) and coercive field (E-C) were also determined. TEM investigations revealed that the average particle size of the polycrystalline powder is 70 nm. The room temperature dielectric constant was found to be 110. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: dielectric properties; Electron microscopy; ferroelectric properties; powders : chemical preparation

Preparation of nanocrystalline ferroelectric BaBi4Ti4O15 by Pechini method - Murugan, A. Vadivel; Navale, S. C.; Ravi, V. (Materials Letters, 2006)
A gel was formed when an aqueous solution of BaCl2, BiNO3, TiOCl2 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 600 degrees C produced the nano crystallites of ternary oxide, BaBi4Ti4O15 (BBT). The phase contents and lattice parameters were Studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at I KHz is 90. The ferroelectric hysteresis loop parameters of these samples were also studied by a home built Sawyer-tower circuit. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: dielectric properties; Electron microscopy; ferroelectric properties; powders chemical preparation

Correlation between multifunctional properties of lead free Iron doped BCT perovskite ceramics - Redhu, Preeti; Punia, Rajesh; Hooda, Ashima; Malik, B. P.; Sharma, Geeta; Sharma, Preeti (Ceramics International, 2020)
Present study investigates the effect of Fe doping on structural, microstructural, dielectric, ferroelectric, piezoelectric and magnetic properties of Barium calcium titanate (BCT) ceramics synthesized by solid state reaction route. The polycrystalline tetragonal structure of prepared ceramics was confirmed from XRD study. Analysis done using Rietveld refinement reveals reduction in lattice parameters as well as unit cell volume on substitution of Fe3+ ions in BCT lattice. Occurrence of four distinct Raman bands viz. 297 cm(-1) -302 cm(-1), 473 cm(-1)-475 cm(-1), 516 cm(-1) -524 cm(-1) and 729 cm(-1) -733 cm(-1) in Raman spectroscopic studies confirms the tetragonal phase of prepared ceramic compositions which are in accordance with XRD study. The Scanning Electron Microscopy analysis revealed polyhedral shaped grains whose average grain size decreased with increase in Fe content (x) in BCT ceramics. A diffused frequency independent phase transition was observed in temperature dependent dielectric measurements. Dielectric properties improved significantly, with shifting of transition temperature, T c close to room temperature with Fe doping. These studiessuggest applications of these ceramics in the development of environment friendly dielectric materials meeting X7R MLCCs specifications. The ferroelectric and piezoelectric properties of these ceramic compositions were found to decrease with increase in Fe concentration. Feeble room temperature ferromagnetism was observed for composition x = 0.020.
Keywords: BCT; dielectric response; Fe doping; ferroelectric properties; Lead free ceramics; Magnetic measurements